2021
DOI: 10.3390/metabo11080470
|View full text |Cite
|
Sign up to set email alerts
|

Phase I In Vitro Metabolic Profiling of the Synthetic Cannabinoid Receptor Agonists CUMYL-THPINACA and ADAMANTYL-THPINACA

Abstract: Synthetic cannabinoid receptor agonists (SCRAs) remain popular drugs of abuse. As many SCRAs are known to be mostly metabolized, in vitro phase I metabolic profiling was conducted of the two indazole-3-carboxamide SCRAs: CUMYL-THPINACA and ADAMANTYL-THPINACA. Both compounds were incubated using pooled human liver microsomes. The sample clean-up consisted of solid phase extraction, followed by analysis using liquid chromatography coupled to a high resolution mass spectrometer. In silico-assisted metabolite iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…SCRAs featuring amino acid amides are subject to extensive metabolic biotransformation, ,, and it is possible that the low in vivo potency of 15 (PX-1) and 19 (PX-2) may be attributed to the rapid biotransformation of these compounds to inactive metabolites. Although 15 (PX-1) and 19 (PX-2) are closely related to several SCRAs that are potent CB 1 receptor agonists in vivo, even small changes in the molecular structure can produce vastly different metabolic profiles and clearance rates. Species differences may also play a role in observed differences because in vitro potencies for the parent compounds at the human CB 1 receptor may not be reflected in mice given the highly idiosyncratic nature of structure–metabolism relationships for this class.…”
Section: Resultsmentioning
confidence: 99%
“…SCRAs featuring amino acid amides are subject to extensive metabolic biotransformation, ,, and it is possible that the low in vivo potency of 15 (PX-1) and 19 (PX-2) may be attributed to the rapid biotransformation of these compounds to inactive metabolites. Although 15 (PX-1) and 19 (PX-2) are closely related to several SCRAs that are potent CB 1 receptor agonists in vivo, even small changes in the molecular structure can produce vastly different metabolic profiles and clearance rates. Species differences may also play a role in observed differences because in vitro potencies for the parent compounds at the human CB 1 receptor may not be reflected in mice given the highly idiosyncratic nature of structure–metabolism relationships for this class.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the ortho and meta positions may be inaccessible to the enzyme due to steric hindrance, for example, nearby dimethyl groups. Monti et al also reported that only one metabolite of CUMYL‐THPINACA with mono‐hydroxylation at the cumyl moiety was detected 23 . However, several metabolites with mono‐hydroxylation at the cumyl moiety have been detected for another synthetic cannabinoids bearing the cumyl moiety 11–13 .…”
Section: Resultsmentioning
confidence: 99%
“…From another perspective, metabolite M3 was proposed to be 13 The ion detected at m/z 393.1997 was indicated as a structure in which one of the carbon atoms was present as a 13 C atom and a chemical formula of 13 mono-hydroxylation at the cumyl moiety was detected. 23 However, several metabolites with mono-hydroxylation at the cumyl moiety have been detected for another synthetic cannabinoids bearing the cumyl moiety. [11][12][13] The developed methods of synthesis and identification will be useful in identifying their structures through the differentiated position of the hydroxyl group at the cumyl moiety.…”
Section: Determination Of Metabolite Structuresmentioning
confidence: 99%
See 2 more Smart Citations